AB0585 High prevalence of psoriatic arthritis in the middle of norway. (23rd January 2014) - Hoff, M.; Kavanaugh, A.; Romundstad, P.; Gulati, A. M.; Haugeberg, G.
Abstract : Background: Studies indicate that the prevalence of psoriatic arthritis (PsA) range from 0.02-0.25 % in various parts of the world [1 ] Objectives: To explore the prevalence of PsA based on the Norwegian population survey "Helse undersøkelsen i Nord Trøndelag" (HUNT-3) performed in 2006-08. Methods: In HUNT 3 an invitation letter was mailed to all 94, 194 adult inhabitants (aged > 20 yrs) in the county Nord-Trøndelag. A total of 50, 806 (54%) responded and answered a questionnaire (Q1) and underwent a brief medical examination. Q1 included questions if patients suffered from psoriasis, rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Patients answering they suffer from psoriasis further answered a second questionnaire (Q2) specific about psoriasis including if they had PsA In order to identify as many patients with PsA as possible we then used the following criteria to identify individual's potential to have PsA: Persons who answered "Yes" or "I do not know" at the question: "Do you have PsA" in Q2. Persons answering that they had psoriasis and RA (Q1). Persons answering that they had psoriasis and AS (Q1). In addition we included persons answering they had psoriasis and cardiovascular disease, but had not filled out Q2. This approach identified 1, 238 patients from HUNT 3. The diagnosis for each identified individual was validated by an experienced rheumatologist (MH) reviewing the medical hospital records in the county. The evaluation was based on joint involvement, serology, X-ray and skin involvement. Treatment and organ manifestations were noticed and the CASPAR criteria were applied. Patients found to have PsA who did not fulfill the CASPAR criteria were evaluated by two rheumatologists (MH and GH). Results: Finally a total of 338 patients were found to have PsA. Mean age was 54 yr, 57.4% were female and disease duration 9, 2 yr. 52.1% were current or previous users of MTX and 18.6% of anti-TNF therapy. 95.6 % fulfilled the Caspar criteria. All the 15 patients evaluated to have PsA without fulfilling the Caspar criteria had psoriasis and arthritis but data on serology was not available. The total prevalence of PsA (per 1, 000) was 6.7 (95% CI 5.9-7.4). Age and gender were distributed as shown in table 1 . Conclusions: The prevalence of PsA in the middle of Norway appears to be higher than previously reported both in Norway [2 ] and other countries[1]. The reason for this is unknown and may include environmental factors, life style factors and genetic differences. Further studies are warranted to explore for these differences in prevalence of PsA. References: Setty AR et al. Curr Rheumatol Rep2007;9(6):449. Madland TM et al. J Rheumatol 2005;32(10):1918 Disclosure of Interest: M. Hoff: None Declared, A. Kavanaugh : None Declared, P. Romundstad: None Declared, A. Gulati: None Declared, G. Haugeberg Grant/research support from: Unrestricted research grant from Pfizer